New Compounds in Eryngium Creticum Lam & Biological Activities Evaluation - Barakat, Salem; Burns, D; Sloul, Zaid (Jordan Journal of Pharmaceutical Sciences, 2021)
The isolation and identification of new 6 compounds from Eryngium creticum lam using LC-MS/MS with positive and negative polarity. Eryngium creticum lam grows wildly in Jordan, are described. The isolated compounds are Isobutyl 3-(diheptylcarbamoyl)benzoate , 3-Nitrophthalic anhydride , Metamitron , 1,3-Diacetylindole , Thebaine and Clemizole. Indentified and evaluated for their cytotoxicity against a panel of in vitro cancer cell lines from Eryngium creticum lam. The methanolic extract was effective against human colorectal cancer cells (HT29 and SW480).